Explaining Dowry Violence in India: Patriarchy, Structural Inequality and Legal Failure - Januari Pratama Nurratri Trisnaningtyas; Gita Kayla Yasmin Otomevia; Salsabila Hayu Adiqoh; Reyvana Noer Oktaviani; Adeline Raj Aura (Universitas Muhammadiyah Tapanuli Selatan, 2026)
Within a family, patriarchal norms place women in an unequal position. At the same time, socio-economic factors such as the caste system and differences in access to education and income reinforce these inequalities. These conditions increase the pressure for domestic violence and control of women, which puts them at risk of death. In addition, at the institutional level, when law enforcement is weak and regulatory implementation is inconsistent, the tendency toward harmful dowry practices will persist. This study examines the tradition of dowry in India as a social practice that encourages gender-based violence in the institution of marriage. Referring to the perspective of radical feminism, this study emphasizes that violence related to the dowry tradition is the result of the interaction between cultural norms, economic conditions, and institutional failure. To identify the structural factors that shape the practice of dowry and its impact, this study uses a literature review method through analysis of academic studies, official crime data, policy documents, and reports on violence against women. The results show that dowries are not only used as a symbol of marriage but also as a mechanism that reproduces economic obligations, gender expectations, and social hierarchies in domestic relationships.